First Incidence of Plum Pox Virus on Apricot Trees in China - Navratil, M; Safarova, D; Karesova, R; Petrzik, K (Plant disease, 2005)
Plum pox disease, caused by Plum pox virus (PPV), is the most severe virus disease of plums, apricots, and peaches. The disease causes heavy losses for fruit growers and the international trade of propagation materials and fresh fruits. PPV was first reported in Bulgaria in 1917 (1). It is now widespread in Europe and has been reported from Cyprus, Syria, Egypt, India, Kazakhstan, Chile, the United States, and Canada. Leaves on symptomatic apricot trees (Prunus armeniaca cvs. Hong Mei and Bai Mei and a selected genotype) in the Hunan Province of China showed typical yellow rings and diffused chlorotic spots. Samples from three suspected trees were repeatedly analyzed using double-antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) and reverse transcription-polymerase chain reaction (RT-PCR) in the summers of 2001-2003. PPV was detected in leaves, bark, and leaf buds of all three trees using ELISA with polyclonal and monoclonal antibodies provided by M. Navratil, Palacky University, Olomouc, Czech Republic (3). The results were confirmed using RT-PCR amplification of a 243-bp of the coat protein gene with a PPV-specific primer pair (2). BLAST analysis of two RT-PCR product sequences (GenBank Accession Nos. AY750961 and AY795603) showed 100% homology to multiple sequences of the PPV-D strain (GenBank Accession Nos. X81080, AF440743, and AF401295). The third sequence (GenBank Accession No. AY795602) had a C at position 112 rather than the T found in the other sequences. The ELISA, RT-PCR, and sequence results indicate that PPV-D was present in the apricot trees. To our knowledge, this is the first indication of PPV occurrence in China. This sporadic incidence of PPV on apricot trees requires addressing problems with the occurrence and spread of plum pox diseases in China and starting an eradication program. References: (1) D. Atanasoff. Annu. Univ. Sofia Fac. Agron. et Sylvic. 11:49, 1932. (2) T. Candresse et al. Phytopathology. 88:198, 1998. (3) I. Hilgert et al. Hybridoma. 12:215, 1993.